2021
DOI: 10.5603/arm.a2021.0036
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Mortality in Patients with Severe COVID-19 Pneumonia—A Retrospective Study

Abstract: Introduction: The novel coronavirus pandemic has caused significant mortality throughout the world. This study was done as there is scarce data on mortality predictors in severe COVID-19 pneumonia patients admitted to ICU in the Indian population. Material and methods: A retrospective study was conducted on COVID-19 pneumonia patients admitted to tertiary care center during June–October 2020. The records of patients admitted to ICU were collected and data included demography, symptoms, comorbidites and vital p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
28
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 28 publications
4
28
1
Order By: Relevance
“…Since December 2019, the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), responsible for the development of coronavirus disease 2019 (COVID-19), has spread globally, resulting in a worldwide health crisis that caused over five million deaths [ 1 ]. The lung is a crucial target organ not only due to the severe bilateral pneumonia observed in 15–30% of hospitalized patients [ 2 , 3 ] but also because it is the site from which the infection spreads to blood vessels, heart, gut, brain, and kidneys [ 4 ]. Published data support interstitial fibrosis with alveolar hyaline membrane (HM) formation as the main underlying histopathologic event responsible for pneumonia and acute respiratory syndrome distress [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since December 2019, the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), responsible for the development of coronavirus disease 2019 (COVID-19), has spread globally, resulting in a worldwide health crisis that caused over five million deaths [ 1 ]. The lung is a crucial target organ not only due to the severe bilateral pneumonia observed in 15–30% of hospitalized patients [ 2 , 3 ] but also because it is the site from which the infection spreads to blood vessels, heart, gut, brain, and kidneys [ 4 ]. Published data support interstitial fibrosis with alveolar hyaline membrane (HM) formation as the main underlying histopathologic event responsible for pneumonia and acute respiratory syndrome distress [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In general, the mortality risk of COVID-19 patients with comorbidities had been reported to be higher than patients without comorbidities [ 3 , 53 , 54 , 55 ]. A study of severe COVID-19 pneumonia showed that of 55% deceased patients, 70% of them had reported having comorbidities (e.g., hypertension, diabetes, ischemic heart disease) [ 56 ]. Another cohort retrospective study of hospitalized COVID-19 patients had reported that 32% of deceased patients had pneumonia [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another cohort retrospective study of hospitalized COVID-19 patients had reported that 32% of deceased patients had pneumonia [ 57 ]. Although relatively high, this number was lower than patients with severe COVID-19 pneumonia [ 56 ]. Their results were similar to our study where COVID-19 pneumonia was a stronger predictor of COVID-19 recovery compared to existing respiratory comorbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Advanced age, as for many other diseases and infections, is a known risk factor for COVID-19 and its complications; it has been observed that the majority of patients affected by severe COVID-19 pneumonia are elderly and that, of all the predictors of mortality in COVID-19 pneumonia, advanced age is the most important [32,33]. This correlation can be explained by the physiological deterioration of one's immune system that occurs with age, as well as by the age-dependent loss of T cells and T cell subtypes [34,35]. Lymphopenia, increased CRP, and erythrocyte sedimentation were observed in the laboratory results of COVID-19 patients [36].…”
Section: Discussionmentioning
confidence: 99%